Characterization of attachment differences of Shiga toxin-producing Escherichia coli (STEC) to pre-chill and post-chill beef tissues - Uhl, Bennett; Unruh, Daniel A.; Phebus, Randall K.; Gragg, Sara E. (My University, 2017)
Shiga toxin-producing Escherichia coli (STEC) has been implicated in beef-related foodborne illness outbreaks. Environmental factors influence bacterial attachment on beef and understanding of bacterial attachment may inform future innervations at the abattoir. This study measured STEC attachment under simulated meat processing conditions on adipose and lean beef tissues. Beef brisket was purchased from a local grocer, and 50 cm2 adipose and lean tissue samples were obtained and stored overnight (18 h; 4ºC). The following day, half of the samples were heated to a surface temperature of 30ºC while the remaining samples were maintained at 4ºC prior to inoculation with 150 µL STEC cocktail (O26, O45, O103, O111, O121, O145, and O157:H7; ca. 7 log CFU/mL) onto the meat surface. Samples were stored at 4⁰C 30 min after inoculation and enumerated at times 0, 3, 5, and 20 min and 1, 3, 8, 12, 24 and 48 h by spread plating loosely attached cells (buffer) and firmly attached cells (homogenized sample) on MacConkey Agar. At every sampling point, each meat sample was shaken for 90 s in a stomacher bag with 0.1% peptone water (PW), transferred into a second stomacher bag with fresh PW, and homogenized. Time*sample type (buffer vs. homogenized sample) was significant (P≤0.001), as STEC cells steadily became more firmly attached throughout the 48 h storage period. Sample type*meat type was statistically significant (P =0.0020) indicating a difference in loose vs. firmly attached populations on lean and adipose tissues; however, the largest difference observed was 0.22 log10 CFU/g. These data demonstrate that the firmly attached STEC population steadily increases on lean and adipose beef tissues over time. Future research should investigate if an increase in firmly attached STEC cells is correlated to reduced intervention efficacy on post-chill carcasses and subprimal cuts, as commonly observed.
Keywords: Spring 2017